The Effects of “I Can Problem Solve Program” on Children’s Perspective Taking Abilities - Ceren Yağmur Aras; Durmuş Aslan (Institute of Advanced Engineering and Science, 2018)
This study was conducted to determine the effects of I Can Problem Solve Program on preschool children’s perspective taking skills. Participants were 51 children who were attending two public preschool. In the study, pretest – posttest – permanence test control group desing was used. There were an experimental group and two control groups in the study. As data collection tool, “Perspective Taking Test for Children (PTC)” which was developed by Aslan and Köksal-Akyol [1] were utilized. Firstly, PTC was applied to children as pretest. Then “I Can Problem Solve Program” which was developed by Shure [2] and adapted to Turkish by Öğülmüş [3] was applied to children in experimental group. Children in control groups were attend the regular program. After the completing the program application PTC was implemented to experimental group and control groups as posttest. Finally, PTC was applied to experimental group as permanence test after a month of posttest. At the end of the study, it was determined that I Can Problem Solve Program had a significant impact on children’s perspective taking skills. There was a statistically significant difference between experimental group and control groups in posttest, while there was no difference between the groups in prettest. Children in experimental group performed better than children in control groups in posttest. Moreover, there was no significant difference in experimental group’s scores between posttest and permanence test scores.